2011
DOI: 10.1002/rcm.5119
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of cyadox by the intestinal mucosa microsomes and gut flora of swine, and identification of metabolites by high‐performance liquid chromatography combined with ion trap/time‐of‐flight mass spectrometry

Abstract: Cyadox (CYX), 2-formylquinoxaline-1,4-dioxide cyanoacetylhydrazone, is an antimicrobial and growth-promoting feed additive for food-producing animals. To reveal biotransformation of CYX in swine intestine, CYX was incubated with swine intestinal microsomes and mucosa in the presence of an NADPH-generating system and swine ileal flora and colonic flora, respectively. The metabolites of CYX were identified using high-performance liquid chromatography combined with ion trap/time-of-flight mass spectrometry (LC/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 27 publications
2
36
1
Order By: Relevance
“…7(C)). The results suggested that the prevailing metabolic pathways of CYX observed in intestinal microflora were the reduction of the N→O group, hydroxylation, hydrolysis and double-bond-reduced reactions, which were consistent with the metabolism study of CYX in vitro by Xu et al [11]. Furthermore, the metabolites detected in intestinal microflora were almost polar-decreased and low molecular weight metabolites, conjecturing that drug effect and toxicity might be strengthened by intestinal microflora.…”
Section: Metabolism Of Cyx By Rat Chicken and Swine Intestinal Microsupporting
confidence: 71%
See 2 more Smart Citations
“…7(C)). The results suggested that the prevailing metabolic pathways of CYX observed in intestinal microflora were the reduction of the N→O group, hydroxylation, hydrolysis and double-bond-reduced reactions, which were consistent with the metabolism study of CYX in vitro by Xu et al [11]. Furthermore, the metabolites detected in intestinal microflora were almost polar-decreased and low molecular weight metabolites, conjecturing that drug effect and toxicity might be strengthened by intestinal microflora.…”
Section: Metabolism Of Cyx By Rat Chicken and Swine Intestinal Microsupporting
confidence: 71%
“…Among the identified metabolites, fourteen metabolites of CYX were detected by intestinal microflora of swine, eight of which were different from the report by Xu et al [11], with seven new metabolites (Cy15, Cy16, Cy19, Cy20, Cy21, Cy23, Cy24) detected for the first time. The possible metabolic pathways of CYX by rat, chicken and swine intestinal microflora were proposed (Fig.…”
Section: Metabolism Of Cyx By Rat Chicken and Swine Intestinal Micromentioning
confidence: 82%
See 1 more Smart Citation
“…Once absorbed, CYA is extensively metabolized in the liver and intestine, producing a number of metabolites, with BDCYA (1,4-bisdesoxycyadox) being the main metabolite and designated as the marker residue in some jurisdictions (Liu et al, 2009;Xu et al, 2012;Wu et al, 2012). BDCYA, the N-oxide reduction product of CYA, is formed by reducing oxygen on both the N1 and N4 sites on the benzene moiety which would lead to DNA damage by intermediate radical production Badham et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Xu et al revealed that when CYA was incubated with swine intestinal microsomes and mucosa in the presence of an NADPH-generating system and swine ileal flora and colonic flora, respectively, three N!O group reduced metabolites (detected in intestinal mucosa, ileal and colonic flora), one hydroxylation metabolite (detected in ileal flora), one hydrolysis metabolite of the amide bond (detected in ileal flora), a new hydrogenation metabolite (detected in colonic bacteria) and a new side-chain cleavage metabolite (detected in colonic bacteria) were identified, indicating that N!O group reduction was the main metabolic pathway of CYA metabolism in swine ileal flora, intestinal microsomes and mucosa (Xu et al, 2011).…”
Section: Metabolic Pathwaysmentioning
confidence: 94%